2018
DOI: 10.1088/1758-5090/aaf44a
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneous hydroxyapatite/alginate composite hydrogel promotes calcified cartilage matrix deposition with potential for three-dimensional bioprinting

Abstract: Calcified cartilage regeneration plays an important role in successful osteochondral repair, since it provides a biological and mechanical transition from the unmineralized cartilage at the articulating surface to the underlying mineralized bone. To biomimic native calcified cartilage in engineered constructs, here we test the hypothesis that hydroxyapatite (HAP) stimulates chondrocytes to secrete the characteristic matrix of calcified cartilage. Sodium citrate (SC) was added as a dispersant of HAP within algi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
75
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(75 citation statements)
references
References 71 publications
0
75
0
Order By: Relevance
“…[5][6][7][8] Thus, the success of osteochondral regeneration is largely dependent upon constructing a scaffold with an ability to recapitulate niche cues. [14][15][16][17] Among a wide array of hydrogels for tissue engineering, gelatin hydrogel has been developed as a variety of bioinks for 3D printing due to its better biocompatibility, biodegradability, bioactivity, and abundance from diverse sources. [9][10][11][12][13] Recently, with rapid development of 3D printing technology, increasing studies, including ours, are focused on fabricating scaffolds by 3D printing of hydrogel bioinks for osteochondral repair.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8] Thus, the success of osteochondral regeneration is largely dependent upon constructing a scaffold with an ability to recapitulate niche cues. [14][15][16][17] Among a wide array of hydrogels for tissue engineering, gelatin hydrogel has been developed as a variety of bioinks for 3D printing due to its better biocompatibility, biodegradability, bioactivity, and abundance from diverse sources. [9][10][11][12][13] Recently, with rapid development of 3D printing technology, increasing studies, including ours, are focused on fabricating scaffolds by 3D printing of hydrogel bioinks for osteochondral repair.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogels are emerging as a promising class of biomaterials for both soft and hard tissue regeneration . Recently, with rapid development of 3D printing technology, increasing studies, including ours, are focused on fabricating scaffolds by 3D printing of hydrogel bioinks for osteochondral repair . Among a wide array of hydrogels for tissue engineering, gelatin hydrogel has been developed as a variety of bioinks for 3D printing due to its better biocompatibility, biodegradability, bioactivity, and abundance from diverse sources.…”
Section: Introductionmentioning
confidence: 99%
“…Recreating this structure (and therefore the associated mechanical function) holds great promise for the creation of durable cartilage implants to treat degenerative diseases like osteoarthritis. On the one hand, both bioprinted cartilage‐specific cells and stem cells demonstrated some ability to deposit hyaline cartilage‐like ECM in vivo, as well as calcified cartilage . Within the field of biofabrication, technologies are being developed to print zone‐specific bioinks, for instance by depositing subsequent layers of inks laden with a gradient in cell concentration, or with different cartilage‐derived and bone‐marrow derived specific progenitor cells, to recreate the native gradient of glycosaminoglycans (GAGs) and the expression of zonal markers .…”
Section: Strategies To Evolve From Shape To Functionmentioning
confidence: 99%
“…On the one hand, both bioprinted cartilage-specific cells and stem cells demonstrated some ability to deposit hyaline cartilage-like ECM in vivo, [ 266 ] as well as calcified cartilage. [ 267 ] Within the field of biofabrication, technologies are being developed to print zone-specific bioinks, for instance by depositing subsequent layers of inks laden with a gradient in cell concentration, [ 268 ] or with different cartilagederived and bone-marrow derived specific progenitor cells, to recreate the native gradient of glycosaminoglycans (GAGs) and the expression of zonal markers. [ 269 ] Further building on these strategies, layering of multiple materials can allow to create osteochondral graft, comprising of closely interconnected bone and cartilage units.…”
Section: Strategies To Evolve From Shape To Functionmentioning
confidence: 99%
“…Sodium citrate was added into ALG as the dispersant of hydroxyapatite (HAP). Eames et al found that the ALG/HAP complex could trigger the chondrocytes to secrete a calcified matrix, which was testified by the favorable survival and proliferation of chondrocytes in the ALG/HAP structure and high expression level of calcified cartilage markers (You et al, 2019). Embedding bone marrow-derived mesenchymal stem cells (bMSCs) in RGD (arginine/glycine/aspartic acid)-functionalized, Îł-ray alginate hydrogels could enhance the osteochondral regeneration and promote the development of a more mechanically functional repair tissue (Critchley et al, 2019).…”
Section: Natural Hydrogels For Cartilage Tissue Engineering Alginatementioning
confidence: 99%